Evaluating Procurement Performance: An Integrated Procurement Maturity Model for Assessing Development Effectiveness and Value for Money - Cook, Bryan; Jackson, Elizabeth; Alexander, Paul (Inderscience, 2024)
This paper introduces a novel integrated procurement maturity model (IPMM) designed to evaluate procurement performance in terms of development effectiveness and value for money. The IPMM incorporates a comprehensive set of key performance indicators, encompassing both qualitative and quantitative measures, to provide a holistic assessment of procurement practices. By integrating various dimensions of procurement maturity, such as strategy, processes, systems, and capabilities, the IPMM enables organisations to identify their strengths and areas for improvement. The IPMM was tested on ten international development organisation and two private sector organisations. The results provide comparative analysis of procurement performance and serve as a potent tool for measuring procurement practices and ultimately improving development outcomes while integrating the concept of value for money.